Peran Penyidik Terhadap Tindak Pidana Perjudian Cap Jie Kia Oleh Kepolisian Resort Sragen - Sawitri, Dwi Yuni Endah; , Dr.Natangsa Surbekti, S.H.,M.Hum (2016)
This study aims to determine the role of investigator in combating the crime of cap jie kia gambling by the Police Resort Sragen, battiers faced by investigators in combating the crime of cap jie kia gambling, and knowing how to prevention and countermeasures of the crime of cap jie kia gambling. This research method using juridical empirical which is descriptive, the type of data in the form of primary data that is interviews and secondary data in the form of primary legal materials, secondary and tertiary. This method collected by interview and literature of study, then data this analyzed by qualitative analysis. The results showed that the factors affecting public gambling cap jie kia due to economic factors, employment is difficult, meager salaries, living conditions of uncertainty, encouraging ordinary people to having imagination advantage with high expectations, by buying lottery (cap jie kia).This effort made by the Investigator Police Sragen with preventive efforts and repressive efforts.